The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00198-009-1042-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density reference ranges for Australian men: Geelong Osteoporosis Study

Abstract: These data supply BMD reference ranges at multiple anatomical sites that will be applicable to white Australian men and similar populations such as USA non-Hispanic white men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 22 publications
3
69
0
1
Order By: Relevance
“…We note that the distribution of bone mineral density is roughly similar in Canada 12 and Australia. 25,26 However, we also note that the geographic variation in fracture does not always reflect underlying variation in bone mineral density. 27 A recent comparison of surveillance rates of hip fracture among Canada, the United States and Germany has shown differences in hip fracture incidence that are both age-and sex-dependent.…”
Section: Discussionmentioning
confidence: 76%
“…We note that the distribution of bone mineral density is roughly similar in Canada 12 and Australia. 25,26 However, we also note that the geographic variation in fracture does not always reflect underlying variation in bone mineral density. 27 A recent comparison of surveillance rates of hip fracture among Canada, the United States and Germany has shown differences in hip fracture incidence that are both age-and sex-dependent.…”
Section: Discussionmentioning
confidence: 76%
“…Whole-body BMD and total hip BMD as well as femoral neck BMD and lumbar spine BMD have been reported as predictors of osteoporosis [7,8,9,10]. Studies have suggested that aging, smoking, alcohol intake, low weight, exercise, and low vitamin D status are putative risk factors for low BMD, but the data are inconsistent [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, this difference may be due to a small group of male patients that are included in the study. On the other hand, the study of the National Health and Nutrition USA (NHANES) III, based on the results of the largest single studies of femoral neck BMD in adult men [23][24][25][26] proves that the peak of BMD at hip and lumbar spine is reached at the age of 20-30 years, while BMD peak of total body and ultradistal radius are reached in men after 30 years. This may explain why our group of patients who haven't reached the peak BMD yet, had higher rates of osteopenia.…”
Section: Discussionmentioning
confidence: 99%